Process modelling of a PVC production plant - Chan, Jun Hoa; Foo, Dominic C. Y.; Kumaresan, Sivakumar; Abdul Aziz, Ramlan; Abu Hassan, Mohd. Ariffin (2005)
This paper presents the modelling of a Polyvinyl Chloride (PVC) resins manufacturing process with batch process simulator, SuperPro Designer V6.0. The simulation model has been developed based on the operating condition of a local PVC manufacturing plant. As the polymerisation process is carried out in batch operation mode, efforts have been made to document the scheduling details of each unit operation and results are presented in the Gantt chart. Cycle time for a complete polymerisation process is determined to be 14.28 hours. The model also reveals that approximately 17 batches of polymerisation reaction can be processed per day, which tallies the real operation of the PVC manufacturing plant.